Pengaruh Motivasi Dan Komitmen Terhadap Efektivitas Kerja Guru SD Negeri Kecamatan Cabangbungin Kabupaten Bekasi - Andri Cahyo Purnomo; Deden Kurnia; Andre Ramadhan (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2018)
This study aims to find and obtain empirical data on the influence (1) motivation, (2) commitment, (3) the effectiveness of teachers of the elementary school of the Branch District of Cabangbungin Bekasi from March to May 2015. Teachers are expected to understand what is motivation, increase commitment to work, and create work effectiveness. Headmaster at SD Negeri Branch Cabangbungin, is expected to help teachers to have high motivation in work, increase commitment, and create work effectiveness. The research method used is quantitative research, using data analysis techniques. This study also uses a causal survey method using an analytical technique. This study used a sample of 97 teachers in 12 State Elementary Schools in Branch District of Cabangbungin selected by using Slovin formula. The results showed that: first, there is a positive influence between the motivation and effectiveness of teachers in school work, this can be demonstrated by the higher the motivation, the better the effectiveness of teachers working at the State Elementary School Branch Cabangbungin District Bekasi. Secondly, there is a positive effect between commitment and effectiveness of teacher work in school. This can be demonstrated by the higher commitment, the better the effectiveness of teachers working at SD Negeri Banggasi Sub-District Cabangbungin. From the results of the study found that the most influential variable is the commitment to the effectiveness of work, this can be proven from the results of statistical calculations with the value of r23 = 0.459, p32 = 0.352 highest compared to the influence of other variables. Third, there is a positive effect between teacher motivation and commitment in school. This suggests that high motivation will increase commitment, recognition of teacher work and appreciation of teachers' work. Follow-up of this research teachers are expected to have a high commitment in carrying out their work with a sense of love, good intentions for worship so as to work maximally in every task without prioritizing the rewards of working wholeheartedly, providing quality educational services to learners for the sake of progress education in Indonesia.